Characterization of ammonium dihydrogen phosphate crystals for soft X‐ray optics of the Beam Expander Testing X‐ray facility (BEaTriX). Issue 3 (14th May 2019) - Ferrari, Claudio; Beretta, Sara; Salmaso, Bianca; Pareschi, Giovanni; Tagliaferri, Gianpiero; Basso, Stefano; Spiga, Daniele; Pelliciari, Carlo; Giro, Enrico
Abstract : A crystal of ammonium dihydrogen phosphate is characterized with respect to its crystallographic quality and the presence of residual strain. The crystal quality is fundamental in view of its use in the BEaTriX X‐ray facility for testing silicon pore optics modules of the ATHENA X‐ray telescope. Abstract : A new type of X‐ray facility, the Beam Expander Testing X‐ray facility (BEaTriX), has been designed and is now under construction at INAF–Osservatorio Astronomico di Brera (Merate, Italy) to perform the acceptance tests of the silicon pore optics modules of the ATHENA X‐ray telescope. Crystals of high perfection and large dimensions are needed in order to obtain a wide beam (20 × 6 cm) with an X‐ray divergence of <0.5′′ and an X‐ray energy purity Δ E / E < 10 −5 . To generate X‐ray diffracted beams at an X‐ray energy of 1.49 keV, ammonium dihydrogen phosphate (ADP) crystals have been considered among other possible choices, because of their reported crystal quality and because they can be grown at sufficiently large size at a reasonable price. In the present paper, the results of the characterization of crystalline quality and lattice planarity of a 20 × 20 × 2 mm ADP sample are reported.